The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijms231710124
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammation and Anti-Pyroptosis Activities of Mangiferin via Suppressing NF-κB/NLRP3/GSDMD Signaling Cascades

Abstract: Mangiferin (MF), a xanthone that extensively exists in many herbal medicines, processes significant activities of anti-inflammation and immunomodulation. The potential regulatory effect and mechanism of mangiferin on cell pyroptosis remain unclear. In this study, mouse bone-marrow-derived macrophages (BMDMs) were stimulated with 1 μg/mL LPS to induce cell pyroptosis and were treated with 10, 50, or 100 μg/mL MF for regulating pyroptosis. The cell supernatants TNF-α, IL-1β, IL-6, and IL-18 were detected by enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…Results from the present study suggested that LPS enhanced the nuclear translocation of NF-κB, as indicated by the elevation of NF-κB levels in the nuclear extract and the increase of NF-κB immunostaining in the nuclei. The present results are consistent with the literature showing that LPS induces the increase in the expression levels of both NF-κB and the NLRP3 inflammasome (46,47). SCM blocked the nuclear translocation of NF-κB induced by LPS.…”
Section: Discussionsupporting
confidence: 93%
“…Results from the present study suggested that LPS enhanced the nuclear translocation of NF-κB, as indicated by the elevation of NF-κB levels in the nuclear extract and the increase of NF-κB immunostaining in the nuclei. The present results are consistent with the literature showing that LPS induces the increase in the expression levels of both NF-κB and the NLRP3 inflammasome (46,47). SCM blocked the nuclear translocation of NF-κB induced by LPS.…”
Section: Discussionsupporting
confidence: 93%
“…Autophagy is a conserved degradation process that maintains cellular homeostasis and the clearance of damaged organelles [ 24 ] and is always accompanied by cell apoptosis, which is a complex process that can promote cell survival or cell death [ 22 ]. In non-neuronal cells, autophagy and apoptosis have been shown to be interconnected by several molecular nodes of crosstalk, enabling the coordinated regulation of cell survival during mild stimulation of autophagy or cell death during excess autophagy [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“… 93 Activation of NLRP3/caspase-1/GSDMD signaling induces secretion of factors such as IL-18 and IL-1β, which activate the NF-κB signaling cascade that mediates inflammation and pyroptosis, causing tissue damage. 94 , 95 Therefore, it was hypothesized that YSHXD can inhibit inflammatory response, reduce kidney injury and delay RF by interfering with pyroptosis. We investigated this hypothesis using a UUO-induced rat model of fibrosis and also in the HK-2 cell fibrosis model.…”
Section: Discussionmentioning
confidence: 99%